KETAHANAN PANGAN PERSPEKTIF UUPA 1960 MELALUI MARHAENISME BUNG KARNO - Moh. Nadir Romadhoni; Ridlo Syukron Fatahillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia's national food security faces structural pressure from the continuing conversion of agricultural land, despite the availability of legal instruments intended to protect it. This article examines the relationship between Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA) and Soekarno's Marhaenism as an ideational framework underlying Indonesia's post-independence land politics, and its relevance to contemporary food security efforts. Using a normative-juridical approach combined with a literature study of statutory regulations, official data, and academic sources, the article finds that the social function principle of land rights in the UUPA is a legal articulation of Marhaenism's ideal of land control by the common people (marhaen), yet its implementation remains suboptimal due to overlapping sectoral regulations, weak enforcement of sustainable agricultural land protection, and the lack of continuity in the agrarian reform agenda across regimes. These findings matter because they show that food security is not merely a technical agricultural issue but also a matter of agrarian legal-political commitment. The article recommends strengthening synchronization between the UUPA, the Sustainable Food Agricultural Land Protection Law, and agrarian reform policy as a unified legal-political framework for food security oriented toward agrarian justice.